A Comparative Study of Renewable Energy Industry Regulation on Feed-In Tariffs Based on Pricing Strategy of Value Standard Method - Peng Sun (Journal of Applied Mathematics)
Based on pricing strategy of value standard method, we establish a three-stage game model of energy production to compare the differences of optimal regulated price and social welfare under three regulation types of feed-in tariffs. We show that the optimal price levels under three main regulation types are different. But the choice of regulation type does not impact the optimal social welfare. So policymakers with different preferences may make regulation decisions in different ways. This successfully explains why many regulation types exist in different countries. Moreover, although it is difficult to determine the optimal price by the value standard method in practice, the conclusions of this paper also provide a judgment criterion for other pricing strategies on how to choose a suboptimal regulation type.